2011
DOI: 10.1159/000324956
|View full text |Cite
|
Sign up to set email alerts
|

An Odorant-Binding Protein as a New Allergen from Siberian Hamster <i>(Phodopus sungorus)</i>

Abstract: A case of anaphylaxis following a bite from a Siberian hamster (SH; Phodopus sungorus) is described. Skin prick tests with hair, urine and salivary gland extracts from SH were positive, while the tests were negative for hair extracts from other rodents. IgE immunoblotting with the patient serum revealed 3 IgE-binding bands of about 18, 21 and 23 kDa. When the patient’s serum was preincubated with rabbit, mouse and gerbil hair extracts, no inhibition of the 3 SH IgE-binding bands was demonstrated. Proteins extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 13 publications
4
21
0
Order By: Relevance
“…However, it is important to remember that extracts from Siberian hamster are not commercially available and must therefore be made in-house. It is also noteworthy that allergens from Siberian hamster do not cross-react with those of the European and Golden hamster or with other lipocalins from cat or dog [2,3]. None of the patients in our study were sensitized to albumin [2,3]; therefore, its role does not seem to be important.…”
Section: To the Editormentioning
confidence: 56%
See 1 more Smart Citation
“…However, it is important to remember that extracts from Siberian hamster are not commercially available and must therefore be made in-house. It is also noteworthy that allergens from Siberian hamster do not cross-react with those of the European and Golden hamster or with other lipocalins from cat or dog [2,3]. None of the patients in our study were sensitized to albumin [2,3]; therefore, its role does not seem to be important.…”
Section: To the Editormentioning
confidence: 56%
“…It is also noteworthy that allergens from Siberian hamster do not cross-react with those of the European and Golden hamster or with other lipocalins from cat or dog [2,3]. None of the patients in our study were sensitized to albumin [2,3]; therefore, its role does not seem to be important. In a recent study by our group [4], only 9% of patients with allergy to cat, dog, and horse were sensitized to albumins.…”
Section: To the Editormentioning
confidence: 56%
“…The Siberian hamster has a mean life span of 2.0-2.5 years (Ross, 1998) and is used in a variety of chronobiological studies (Butler & Zucker, 2009;Grone et al, 2011;Ruby et al, 2008;Schöttner et al, 2011;Tups et al, 2012) and in research on the evolution of parental behaviour (Ma et al, 2005;Stulberg & Wynne-Edwards, 1998;WynneEdwards & Lisk, 1989), parasite susceptibility (Ike et al, 2005;Uchida et al, 2003) and cancer (Kondo et al, 2008(Kondo et al, , 2009. As the popularity of the Siberian hamster increased as a household pet, there has been a corresponding increase in reports on Siberian hamster-associated respiratory allergic disease (Bertó et al, 2002) and bite-induced anaphylaxis in humans (Lim et al, 2004;Niitsuma et al, 2003;Torres et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although a growing number of patients present to outpatient clinic with symptoms of SH allergy, there is little information about the allergens involved. The allergic symptoms caused by SH varies from upper and lower respiratory tract symptoms (4) to anaphylaxis after bites (5)(6)(7). In these reports, IgE-binding bands ranging from 18 to 32 kDa were described as the responsible allergens, although the specific allergens were not identified.…”
mentioning
confidence: 99%
“…Torres et al (7) characterized three IgE-binding bands found in SH hair, urine, and salivary glands. These bands have molecular masses of ϳ18, 21, and 23 kDa.…”
mentioning
confidence: 99%